Influence of frailty in older patients undergoing emergency laparotomy: a UK-based observational study. Issue 10 (6th October 2017) - Parmar, Kat L; Pearce, Lyndsay; Farrell, Ian; Hewitt, Jonathan; Moug, Susan
Abstract : Introduction: The National Emergency Laparotomy Audit (NELA) has reported that older patients (≥65 years) form a large percentage of emergency high-risk cases with increased postoperative morbidity and mortality. With the population continuing to age rapidly, it is clear that a greater understanding of the factors affecting surgical outcomes in older patients is required. Frailty is a relatively new concept taking into account a variety of factors that increase an individual's vulnerability to increased dependency and death. Research has suggested that high frailty scores increase postoperative complications, length of stay and mortality but the majority of these studies have been carried out on elective patients. Knowledge of how frailty affects patients in an emergency setting would aid clinicians' and patients' decision-making process. Methods and analysis: This multicentre study will include consecutive adult patients aged 65 years and over undergoing emergency laparotomies over a 3-month period at 52 National Health Service hospitals across the UK. The primary outcome will be 90-day mortality. Secondary outcomes will include length of hospital stay, 30-day complications, change in level of independence and 30-day readmission. This study has been powered to detect a 10% change in mortality associated with frailty (n=500 patients). Ethics and dissemination: This study has been approved by the National Health Service Research Ethics Committee. It has been registered centrally with HRA for English sites, NRSPCC for Scottish sites and Health and Care Research Permissions Service for sites in Wales.Dissemination will be via international and national surgical and geriatric conferences. In addition, manuscripts will be prepared following the close of the project. Trial registration number: This study is also registered online at www.clinicaltrials.gov (registration number NCT02952430 ).